Affective bonds in adulthood: the visitor of the patient with aids - Silveira, Edilene A.A.; Carvalho, Ana M.P. (Brazilian Journal of Sexually Transmitted Diseases, 2003)
Introduction: Relatives friends visits to patients provide emotional self-assurance, tranquility and a release of emotional tension. The close people create strong bounds and supporting links that may cooperate in the hcalth overcoming and the readmission of a positive-HlV person into social groups. However, factors like the stigma make this cooperation and adaptation difficult for lhe person living with the HIV/aids. Objective: The present sludy had as a goal comprehend the experience of visiting an adult patient hospitalized due to aids. Methods: It had as a thcorical basis lhe social representation defined by Spink, and was devcloped by a positive HIV committing unit in a Ribeirão Preto (SP) general hospital. Rcsults: The feelings presented were based on the living of the relalionship with the sick person and on the composition of the disease in the sociely. Conclusion: Thcy generate necessities that must be attend by the nurse as an indirect form of promoving the sick person’s overcoming.